Avoiding the Trap of Misdiagnosis: Valuable Teaching Points Derived from a Case of Longstanding Popliteal Artery Entrapment Syndrome - Heitham Wady; Zain Badar; Zerwa Farooq; Palma Shaw; Katsuhiro Kobayashi (Case Reports in Medicine)
Popliteal artery entrapment syndrome (PAES), a condition predominantly affecting young individuals, is a rare clinical entity that can result in significant morbidity. The presence of lower limb pain and claudication in young, physically active individuals should prompt consideration for PAES. Early diagnosis and management is crucial to prevent long-term complications; however, diagnosis is fraught with challenges due to the rarity of the disease and its similar clinical presentation with more common conditions. We present a case of a young female with PAES who was misdiagnosed and underwent a tarsal tunnel release for suspected tarsal tunnel syndrome and subsequent fasciotomies for presumed chronic exertional compartment syndrome (CECS) without any relief. We outline the insidious undiagnosed course of her condition over a period of 12 years, discuss teaching points of how to recognize key differences of PAES and associated conditions, and provide recommendations for how to make the right diagnosis.